Al2O3/Cu-O composites fabricated by pressureless infiltration of paper-derived Al2O3 porous preforms. Issue 17 (1st December 2018) - Pfeiffer, Stefan; Lorenz, Hannes; Fu, Zongwen; Fey, Tobias; Greil, Peter; Travitzky, Nahum
Abstract: Al2 O3 /Cu-O composites were fabricated from the paper-derived alumina matrix infiltrated with a Cu-3.2 wt% O alloy. Paper-derived alumina preforms with an open porosity ranging from ∼ 14 to ∼ 25 vol% were prepared by sintering of alumina-loaded preceramic papers at 1600 °C for 4 h. Pressureless infiltration at 1320 °C for 4 h of the preforms with Cu–O alloy resulted in the nearly dense materials with good mechanical and electrical properties, e.g. fracture toughness up to 6 MPa m 0.5, four-point-bending strength up to 342 MPa, Young's modulus up to 281 GPa and electrical conductivity up to 2 MS/m depending on the volume fraction of copper alloy in the composites. The technological capability of this approach was demonstrated using prototypes in various engineering fields fabricated by lamination, corrugating and Laminated Object Manufacturing (LOM) methods.